Diabetes mellitus: The pathophysiology as a canvas for management elucidation and strategies - Franklyn Nonso Iheagwam; Olawumi Toyin Iheagwam (Medicine in Novel Technology and Devices)
Diabetes mellitus (DM) is a progressive metabolic disease characterised by high blood glucose due to autoimmune destruction of the β-islet of Langerhans or gradual development of insulin resistance and β-cell degeneration. Numerous risk factors, from genetic to environmental, are associated with this disease. Based on the global observed cases and etiopathogenesis, DM falls into three broad categories: type 1, 2, and gestational diabetes mellitus. A comprehensive search was used to identify relevant publications using targeted keywords associated with DM, pathophysiology, medication, characterised compounds, and others across prominent databases like PubMed, Scopus, and Web of Science. This review examines how DM pathophysiology influences the type of diagnosis, screening, treatment, and management regimen that is implemented. The link between DM and some mechanistic factors and activated glucose metabolic changes is discussed. Insights on the medications targeting various DM pathophysiology mechanisms, antidiabetic mechanisms of characterised compounds from natural products and computer-aided identification of antidiabetics from natural sources are reviewed. These findings could lay the groundwork for inventive therapeutic strategies and leads from natural products based on the proper elucidation of antidiabetic mechanisms, thereby improving management and the impact of DM.